2015
DOI: 10.1371/journal.pone.0124837
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Induced Premature Senescence Is Associated with DNA Damage Mediated SIRT1 and SIRT2 Down-Regulation

Abstract: The natural polyphenolic compound resveratrol (3,4,5-trihydroxy-trans-stilbene) has broad spectrum health beneficial activities including antioxidant, anti-inflammatory, anti-aging, anti-cancer, cardioprotective, and neuroprotective effects. Remarkably, resveratrol also induces apoptosis and cellular senescence in primary and cancer cells. Resveratrol’s anti-aging effects both in vitro and in vivo attributed to activation of a (NAD)-dependent histone deacetylase family member sirtuin-1 (SIRT1) protein. In mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 42 publications
2
32
1
Order By: Relevance
“…28 However, a recent report indicated that increase in SIRT2 levels in aged rat brain is specific only to occipital region and no other regions. 36 In contrast to the results of our study, a recent report by Kilic Eren et al, (2015) 37 showed decrease in SIRT2 levels in resveratrol induced premature senescence in human fibroblasts. Thus, the reports are contradictory and in general the published reports till now point toward role of SIRT2 loss or overexpression as a cause for senescence induction.…”
Section: Discussioncontrasting
confidence: 99%
“…28 However, a recent report indicated that increase in SIRT2 levels in aged rat brain is specific only to occipital region and no other regions. 36 In contrast to the results of our study, a recent report by Kilic Eren et al, (2015) 37 showed decrease in SIRT2 levels in resveratrol induced premature senescence in human fibroblasts. Thus, the reports are contradictory and in general the published reports till now point toward role of SIRT2 loss or overexpression as a cause for senescence induction.…”
Section: Discussioncontrasting
confidence: 99%
“…The effects of RES on cellular senescence have been widely investigated, although the results are contradictory. Multiple studies, including our own, have pointed out that RES can attenuate cell ageing; other have demonstrated that it can actually induce senescent phenotype, but in cancer cell lines . However, the molecular mechanisms responsible for that activity were not fully elucidated.…”
Section: Discussionmentioning
confidence: 95%
“…RV was also found to induce premature senescence via decreasing SIRT1 and SIRT2 levels in human dermal fibroblasts. The decline in SIRT1/2 expression in response to RV treatment showed that DNA damage was regulated by RV (38). Kao et al (39) reported that RV treatment reduced oxidative stress in human endothelial cells via induction of SIRT1 activation in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%